1962
DOI: 10.1103/physrev.128.1568
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance of Manganese in Gallium Arsenide

Abstract: The paramagnetic spin-resonance spectra of manganese in GaAs have been studied at 77 °K. Isotropic values for the spectroscopic splitting factor g and for the hyperfine interaction constant A have been measured to be 2.004 and 56 G, respectively. Fine structure lines were not found, even at 4°K. A spin Hamiltonian describing the resonance spectra is given. An estimate of the cubic splitting constant a is deduced from the angular variation of the spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
8

Year Published

1972
1972
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 4 publications
3
23
0
8
Order By: Relevance
“…Covalency leads to a partial filling of the 4s orbital, and causes a decrease in the observed magnitudes of A ║ and A ⊥ . Our hyperfine values are very similar to the Mn 2+ values found in GaAs and GaP [37,38], thus verifying that the covalency in CdGeAs 2 is comparable to the covalency in GaAs and GaP. Figure 4 shows an ENDOR spectrum, from the M S = +3/2 manifold, that contains lines from nearby Cd and As neighbors.…”
Section: Originalsupporting
confidence: 78%
“…Covalency leads to a partial filling of the 4s orbital, and causes a decrease in the observed magnitudes of A ║ and A ⊥ . Our hyperfine values are very similar to the Mn 2+ values found in GaAs and GaP [37,38], thus verifying that the covalency in CdGeAs 2 is comparable to the covalency in GaAs and GaP. Figure 4 shows an ENDOR spectrum, from the M S = +3/2 manifold, that contains lines from nearby Cd and As neighbors.…”
Section: Originalsupporting
confidence: 78%
“…Its ground state is a spin sextet 6A1 (S = 5/2, L = 0). The EPR spectra characteristic of A -(d5 ) were observed for GaP as well as for GaAst [33,34]. It seems therefore rather well established that for bulk GaAs manganese impurity occurs either as a neutral (d5 d-h) or ionized (d5 ) acceptor center.…”
Section: The Nature Of Mn Impuritymentioning
confidence: 92%
“…Manganese impurity in III-V compounds has been studied for a long time [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. The present understanding of the situation can be summarized as follows: There are essentially three types of Mn centers in III-V compounds.…”
Section: The Nature Of Mn Impuritymentioning
confidence: 99%
“…23,24 Fedorych et al 24 found for their partially compensated LT-MBE Ga 1−x Mn x As samples with 10 −4 Ͻ x Ͻ 10 −3 a linear dependence of D 001 = ͑96.3x + 0.112͒ mT ϫ g B on x. An extrapolation of this behavior into the concentration range of our MOVPE-grown sample ͑x = 0.0027 from EPR͒ would predict D 001 Ϸ 0.37 mTϫ g B , which is substantially larger than ͉D 001 ͉ = 0.1 mTϫ g B determined by our simulation.…”
Section: Eprmentioning
confidence: 99%